Alcohol and community football in Australia. (June 2014) - Nicholson, Matthew; Hoye, Russell; Brown, Kevin M
This paper focuses on spectators' alcohol use at a regional community football (Australian Rules) club in Victoria, Australia, in the context of a season-long trial to sell only mid-strength (and not full-strength) beer at the ground during home games. Both quantitative and qualitative data were collected on spectators' alcohol choices and preferences together with experiences and attitudes towards the trial. A minority (31%) usually drank alcohol while watching the game and 75% of all supporters agreed with the supply of alcohol at football grounds. Full-strength beer was the drink of choice for 70% of drinkers and faced with a restricted choice of alcohol for purchase (that did not include full-strength beer), 44% reported they would choose full-strength mixed drinks as an alternative. Choosing higher alcohol content drinks if the usual choice was not available was also found in the case of mid-strength beer drinkers, half of whom would choose full-strength beer if mid-strength was unavailable. In bivariate correlations, women, those aged 30–39 years, home supporters and those who did not drink alcohol while spectating were significantly more likely to support the trial. In a regression model the significant predictors were refined to being: female, a non-drinker and aged 50–59 years. Qualitative data supported the idea that the trial had been successful in terms of supporter acceptance of the move to cease the sale of full- strength beer and indicated that the club's relatively supportive and 'family friendly' culture was a key in overcoming earlier opposition to the trial. While the results of this evaluation are mainly positive, the club's particular culture and leadership suggest that its experience may not be transferred in any automatic sense to other clubs both within and without its league where more 'traditional' patterns associated with masculinity and alcohol use may be more persistent and prevalent.